Предмет: Алгебра,
автор: kqyuantt
(x+2)^2=(x-6)^2 Помогите пожалуйста
Ответы
Автор ответа:
0
раскрываем скобки
x^2+4x+4=x^2-12x+36
переносим с противоположными знаками
x^2+4x+4-x^2+12x-36=0
сокращаем
16x-32=0
16x=32
x=32:16
x=2
x^2+4x+4=x^2-12x+36
переносим с противоположными знаками
x^2+4x+4-x^2+12x-36=0
сокращаем
16x-32=0
16x=32
x=32:16
x=2
Похожие вопросы
Предмет: Математика,
автор: p26350503
Предмет: Алгебра,
автор: maynameruslan
Предмет: Математика,
автор: 333479
Предмет: Математика,
автор: namail